DISCUSSION OF THE ANALYSIS OF THE PRODUCTION AND SALE OF ALCOHOL AND TOBACCO PRODUCTS IN UZBEKISTAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article states that excise taxes are included in the price of excise goods and thus passed on to final consumers. At the same time, general information about the analyzes conducted on the production and sale of alcohol and tobacco products in Uzbekistan is given. The study includes a comprehensive examination of market dynamics, regulatory frameworks, industry players and socio-economic factors affecting these two sectors.Excise tax plays an important role in the formation of state revenues and regulation of consumption of certain goods and services. This article outlines the main directions for improving the control mechanisms of the excise tax administration, focusing on policy reforms integration and capacity building in tax authorities.